2015
DOI: 10.1111/acv.12244
|View full text |Cite
|
Sign up to set email alerts
|

Reintroducing reintroductions into the conservation arena

Abstract: Read the Feature Paper: Defining reintroduction success using IUCN criteria for threatened species: a demographic assessment and the Commentaries on this Feature Paper: Using the IUCN Red List criteria to assess reintroduction success; Alternative perspectives on reintroduction success; Developing a standard for evaluating reintroduction success using IUCN Red List indices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Our review highlights the deficit of peer‐reviewed articles that assess ecosystem‐level consequences of keystone species reintroductions, a bias toward mammals as a focal taxon, and a bias toward studies conducted in the United Sates. While studies of population dynamics of reintroduced keystone species are important to inform managers about the success of reintroductions (Long et al ; Hale ), more studies must focus on ecosystem‐level effects of reintroductions (Robert et al ) so that the presence, extent, and rate of ecosystem restoration driven by keystone species can be understood. Additionally, studies conducted on a wider variety of taxonomic groups, and in other geographic regions, would add to the understanding of keystone species worldwide, and increase knowledge in areas of high conservation concern where studies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Our review highlights the deficit of peer‐reviewed articles that assess ecosystem‐level consequences of keystone species reintroductions, a bias toward mammals as a focal taxon, and a bias toward studies conducted in the United Sates. While studies of population dynamics of reintroduced keystone species are important to inform managers about the success of reintroductions (Long et al ; Hale ), more studies must focus on ecosystem‐level effects of reintroductions (Robert et al ) so that the presence, extent, and rate of ecosystem restoration driven by keystone species can be understood. Additionally, studies conducted on a wider variety of taxonomic groups, and in other geographic regions, would add to the understanding of keystone species worldwide, and increase knowledge in areas of high conservation concern where studies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…To address several calls for an agreeable set of well-defined reporting criteria for reintroductions (Bubac et al, 2019;Morris et al, 2021;Robert et al, 2015;Seddon et al, 2007), we identified and categorized methodological consistencies from systematically reviewed studies to develop a framework for evaluating large carnivore reintroductions. This evaluation framework included a full suite of stages, indicators, and targets, along with referenced justification for all inclusions across as many species as possible (Figure 1).…”
Section: Phase Ii: Standardized Frameworkmentioning
confidence: 99%
“…With climate change as an important concern for species conservation (Bellard et al., 2012; Thomas et al, 2004; Thuiller et al., 2005; Urban, 2015), translocations represent an opportunity for practitioners to contribute to the migration of populations towards the poles, or higher up in altitude, to cooler climatic conditions, thus mitigating the deleterious effects of warming (Aitken & Whitlock, 2013; Brooker et al, 2011; Fahselt, 2007). Review articles on plant translocations have focused on an assessment of the success of translocations, and the factors determining that success (Dalrymple et al., 2011; Godefroid et al., 2011; Menges, 2008; Silcock et al., 2019), although the criteria for success are themselves a subject of debate (Haskins, 2015; Robert et al., 2015a, 2015b; Seddon, 2015; Shier, 2015). Curiously, no studies are available that examine the geographical and climatic differences between the natural origins of translocated plant material and its final destination.…”
Section: Introductionmentioning
confidence: 99%